Self-Medication Practices in Medical Students During the COVID-19 Pandemic: A Cross-Sectional Analysis - Yasmin, Farah; Asghar, Muhammad Sohaib; Naeem, Unaiza; Najeeb, Hala; Nauman, Hamza; Ahsan, Muhammad Nadeem; Khattak, Abdullah Khan (Frontiers in Public Health, 2022)
Background and Objectives During the pandemic, the growing influence of social media, accessibility of over-the-counter medications, and fear of contracting the virus may have led to self-medication practices among the general public. Medical students are prone to such practices due to relevant background knowledge, and access to drugs. This study was carried out to determine and analyze the prevalence of self-medication practices among medical students in Pakistan. Materials and Methods This descriptive, cross-sectional study was conducted online in which the participants were asked about the general demographics, their self-medication practices and the reasons to use. All participants were currently enrolled in a medical college pursuing medical or pharmacy degree. Non-probability sampling technique was used to recruit participants. Results A total of 489 respondents were included in the final analysis. The response rate was 61%. Majority of the respondents were females and 18–20 years of age. Self-medication was quite prevalent in our study population with 406 out of 489 individuals (83.0%) were using any of the drugs since the start of pandemic. The most commonly utilized medications were Paracetamol (65.2%) and multivitamins (56.0%). The reasons reported for usage of these medications included cold/flu, or preventive measures for COVID-19. The common symptoms reported for self-medication included fever (67.9%), muscle pain (54.0%), fatigue (51.7%), sore throat (46.6%), and cough (44.4%). Paracetamol was the most commonly used drug for all symptoms. Female gender, being in 3rd year of medical studies, and individuals with good self-reported health were found more frequent users of self-medication practices. Conclusion Our study revealed common self-medication practices among medical and pharmacy students. It is a significant health issue especially during the pandemic times, with high consumption reported as a prevention or treating symptoms of COVID-19.